2017
DOI: 10.14701/ahbps.2017.21.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Safety of duodenal ampullectomy for benign periampullary tumors

Abstract: Backgrounds/AimsSurgical resection, such as pancreaticoduodenectomy (PD), is used for treatment of benign periampullary tumors, but high morbidity and mortality resulting from PD can be a huddle. The aim of this study is to suggest a safe and less invasive procedure for treatment of benign periampullary tumors.MethodsFrom January 2001 to September 2016, 31 patients with ampulla of Vater (AOV) tumors were reviewed retrospectively. Patients who were confirmed with malignancy through biopsy were excluded, except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…After screening of titles and abstracts, 367 studies remained. Finally, 59 papers were eligible to be included into the meta-analysis after full-text evaluation (42 EA, 8 SA, 1 PD, 3 SA + PD, 4 EA + SA, 1 EA + PD; Figure 1 PRISMA chart) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ...…”
Section: Resultsmentioning
confidence: 99%
“…After screening of titles and abstracts, 367 studies remained. Finally, 59 papers were eligible to be included into the meta-analysis after full-text evaluation (42 EA, 8 SA, 1 PD, 3 SA + PD, 4 EA + SA, 1 EA + PD; Figure 1 PRISMA chart) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ...…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, data of surgical ampullectomies are very few, and included between 11 and 44 patients per case series with an R0rate between 63 and 100% (39,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). Overall complications were between 9 and 68% but 30-day-mortality often was missing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the new trials have limitations due to the small number of patients. The different guidelines for various lesions were applied in eligible studies, and the therapeutic effects of ER and SR can be variable according to the reports [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In the current study, the overall information for the therapeutic effect and complication of ER was obtained through a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection (SR) can have the possibility of complete resection, SR has higher morbidity and mortality compared to endoscopic resection (ER) [ 6 , 7 ]. In previous studies, ER showed a wide range of complete resection from 9.1% to 98.4% [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The various factors can impact on variable rates.…”
Section: Introductionmentioning
confidence: 99%